Study On Malaysian Urban Rainfall-Runoff Characteristics: Case Study Of Sungai Kayu Ara, Damansara, Selangor - Leong, Weng Chin (2007)
Knowledge on the rainfall spatial and temporal distribution, as well as the rainfall-runoff response, is vital in engineering practices for developing area in the humid tropics. Nevertheless, this study will primarily discuss the runoff response due to varying rainfall within small urban catchment in Malaysia. Daily totals rainfall and 10- min intervals rainfall and runoff data from year 1996 to 2004 had been analysed. The result shows that greater rainfall volume fell on developed area, compared to suburban/rural area. This is proven that most of proportion of annual rainfall extent is contributed by strong convective storm during the inter-monsoon season. The relationship between direct runoff and mean areal rainfall was developed and validated using statistical model (SPSS®). To verify the representativeness of rainfall-runoff response, rainfall concentration between the developed area and suburban/rural area was determined. Analyses of constant loss rates indicate that the generation of cumulative direct runoff can be attributed to the constant rainfall intensities. The correlation between the derived runoff coefficients and rainfall intensities was made. This was to assess the Design Chart 14.3 for peak flow estimation in the Malaysian Urban Stormwater Management Manual (MSMA). The distribution percentage of observed data among classified land uses in the relevant design chart is found to have corresponded quite well with the degree of land use covers, estimated from digital topographic information. This implies that, the runoff coefficient versus intensity chart adopted from the Australian Rainfall and Runoff 1977 is still in the suitable range for use in Malaysian urban condition. To ensure a future need for higher design requirement in urban stormwater control facilities, the catchment response subjected to development was determined. Factors such as rainfall volume and its temporal and spatial distribution of rainfall were taken into account for this purpose. The increasing peak flow with corresponding time-to-peak resulted from seven (7) to eight (8) years' urbanization had been successfully identified.